Addressing context dependence in ecology. (February 2022) - Catford, Jane A.; Wilson, John R.U.; Pyšek, Petr; Hulme, Philip E.; Duncan, Richard P.
Abstract : Context dependence is widely invoked to explain disparate results in ecology. It arises when the magnitude or sign of a relationship varies due to the conditions under which it is observed. Such variation, especially when unexplained, can lead to spurious or seemingly contradictory conclusions, which can limit understanding and our ability to transfer findings across studies, space, and time. Using examples from biological invasions, we identify two types of context dependence resulting from four sources: mechanistic context dependence arises from interaction effects; and apparent context dependence can arise from the presence of confounding factors, problems of statistical inference, and methodological differences among studies. Addressing context dependence is a critical challenge in ecology, essential for increased understanding and prediction. Highlights: 'Context dependence' is widely used to describe disparate results in ecology, but the term is poorly defined and inconsistently used. Context dependence arises when ecological relationships vary in magnitude or sign, depending on the conditions under which they are observed. Context dependence can result from multiple factors and processes, so, unless the underlying causes are identified, concluding that relationships are context dependent provides limited understanding. We distinguish between apparent and mechanistic context dependence, with the former an artefact of study design and approach and the latter reflecting ecological interaction effects. Recognising and addressing the different sources of context dependence should facilitate increased understanding, prediction, and generalisation in ecology.